INVENTORY CONTROL APPLICATION ARCHITECTURE USING A WEB-BASED METHOD OF SAFETY STOCK AT YUNI STORE - Indra Halid Triyatno Lauhatta; Henry Bambang Setyawan; Tony Soebijono (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Toko Yuni is a motor vehicle spare parts store in Central Maluku District that sells goods in the form of motorcycle vehicle tools of Honda, Yamaha and Suzuki brands. Customers mention goods to be purchased to employees, then employees take the goods on display shelves in accordance with customer demand, after that employees record the name of goods, the amount of goods and prices of goods purchased into a piece of paper then calculated using a calculator. The business process is still going wrong when recapitulating daily transactions resulting from missing selling note, it often happens to run out of supplies of merchandise and the goods can accumulate. The solution of these problems is with an application that can record the receipt of goods and sales of goods by applying inventory control using safety stock. with safety stock, inventory will not run out of goods, the system will provide notification in the form of alerts when inventory has reached safety stock.